Kształtowanie oczekiwań inflacyjnych przez prognozy inflacji w świetle badań empirycznych - Szyszko, Magdalena (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The article focuses on aspects of modern monetary strategy: inflation expectationsand inflation forecasts. Inflation forecasts’ main function is shaping inflationexpectations. The deeper the impact of a central bank on expectations, the easierits task of stabilization of inflation on the targeted level. The article presents theresults of empirical research that verifies the hypothesis on existence of interdependencesof inflation forecasts and inflation expectations. The research coverstwo countries: Sweden and the Czech Republic. The research methodology includesquantitative methods: quantification of expectations (Carlson-Parkin method)and non-parametric statistics of interdependences. The research confirms theexistence of statistically important interdependences of inflation forecasts andexpectations in both countries. Their strength is remarkable for Sweden (c.a. 0.70)and much weaker for the Czech Republic (c.a. 3.0).